ALGORITHMS FOR THE FORMATION OF THE ENTERPRISE IMAGE ON THE DOMESTIC AND FOREIGN MARKETS OF ECOLOGICALLY FRIENDLY PRODUCTS (INNOVATIVE ECONOMY, 2025)
Kryvous V.B.  ALGORITHMS FOR THE FORMATION OF THE ENTERPRISE IMAGE ON THE DOMESTIC AND FOREIGN MARKETS OF ECOLOGICALLY FRIENDLY PRODUCTS Purpose. The aim of the article is to distinguish algorithms for formation of a positive image of the enterprise for the production of ecologically friendly products and the implementation of a targeted impact on the consciousness of the consumer in order to achieve competitive advantages, a high level of sales of goods in the domestic and foreign markets in the conditions of modern changes in the priorities of society and growing competition in ecological markets.Methodology of research. A systematic approach that is used in the research is aimed at comprehensive understanding for the formation of a positive image of enterprises producing ecologically friendly products of Ukraine and their promotion on domestic and foreign ecological markets. Factor analysis was applied to improve approaches to algorithms choice for image formation of enterprises in ecological markets; statistical analysis to assess the state of the ecologically friendly products market of individual countries; an abstract and logical method was used to generalize the results and formulate research conclusions.Findings. The peculiarities of forming a positive image of the enterprise for the production of ecologically friendly products of Ukraine, its promotion on domestic and foreign markets are revealed. Complex relations with consumers are defined as a component of the company's success formula.Originality. The theoretical support of algorithms for the formation of a positive image of the enterprise in the conditions of work on domestic and international ecological markets has gained further development.Practical value. The results of the research can be used in the preparation of methodological and educational materials related to this issue, as well as by enterprises that are on the way to forming their own image in the markets of ecologically friendly products.Key words: reputation, image, brand, ecologically friendly products, foreign markets.
Keywords: reputation; image; brand; ecologically friendly products; foreign markets.